Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Sektor Pariwisata di Provinsi Bali Periode 2013-2018 - Wahyuni, Ni Kadek; Wardana, I Gede (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 1 (2022): VOL 11 NO 1, JANUARI 2022 [1-403 ]DO - 10.24843/EEP.2022.v11.i01.p08, 2022)
This study aims to determine the effect of the number of tourist visits, the number of tourist travel agencies, and the US Dollar exchange rate on the income of tourism in Bali Province when the disaster of the Mount Agung eruption occurred. The research uses panel data in the time series data from 2013-2018 and cross section 9 Districts / Cities in Bali Province. Multiple linear regression analysis techniques obtained the simultaneous of tourism sector influenced by the number of tourist visits, the number of travel service bureaus, and the US Dollar exchange rate. This result shows the increase in tourism activities for income of the tourism sector. There is a partial influence on the number of tourist visits and the number of tourist travel agencies on the income of tourism sector, while there is no influence in the partial of the US Dollar exchange rate on the income tourism in Bali Province.